2021
DOI: 10.1002/glia.24039
|View full text |Cite
|
Sign up to set email alerts
|

Histamine triggers microglial responses indirectly via astrocytes and purinergic signaling

Abstract: Histamine is a monoaminergic neurotransmitter which is released within the entire brain from ascending axons originating in the tuberomammillary nucleus in a sleep state‐dependent fashion. Besides the modulation of neuronal firing patterns, brain histamine levels are also thought to modulate functions of glial cells. Microglia are the innate immune cells and professional phagocytes of the central nervous system, and histamine was previously shown to have multiple effects on microglial functions in health and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…To this end, we have previously demonstrated sexually dimorphic differences between male and female Nf1 ± neurons [15], which reflect sex by genotype effects on cyclic AMP generation and dopamine homeostasis. Additional studies will be necessary to determine whether differences in neuronal dopamine (or other paracrine factors) underlie the sexually dimorphic differences observed in microglia [2,19,39,40,64,69]. Understanding how this intercellular crosstalk is established and maintained will provide new insights into our understanding of sex differences and the interplay between risk factors and cellular function in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we have previously demonstrated sexually dimorphic differences between male and female Nf1 ± neurons [15], which reflect sex by genotype effects on cyclic AMP generation and dopamine homeostasis. Additional studies will be necessary to determine whether differences in neuronal dopamine (or other paracrine factors) underlie the sexually dimorphic differences observed in microglia [2,19,39,40,64,69]. Understanding how this intercellular crosstalk is established and maintained will provide new insights into our understanding of sex differences and the interplay between risk factors and cellular function in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia express purinergic receptors, such as P2X7, P2Y6, and P2Y12, whose downstream signal triggers microglial phagocytosis (Haynes et al, 2006 ; Koizumi et al, 2007 ; Rajbhandari et al, 2014 ). It is reported that activated astrocytes secreted ATP to enhance phagocytic activity of microglia via P2Y12 purinergic receptor (Figure 4b ) (Xia et al, 2021 ). Astrocyte‐derived ATP also assists microglial phagocytosis by acting as a chemoattractant for microglia to the site of phagocytosis.…”
Section: Interactive Regulation Between Astrocytes and Micro...mentioning
confidence: 97%
“…In addition, the excitatory neurotransmitter glutamate is released from astrocytes and has been reported to cause microglial activation in a TNF-α–dependent manner, resulting in neuroinflammation and unbalanced neurotoxicity ( 51 ). Histamine, a monoamine neurotransmitter, is known to regulate microglial histamine responses mediated by histamine receptor isoform 1, which is expressed mostly on astrocytes ( 52 ). These observations suggest that an unbalanced neurotransmitter system affects glial cross-talk ( Fig.…”
Section: Neuroinflammatory Interactions In the Nvu And Their Associat...mentioning
confidence: 99%